The Effect of the 5E Learning Model on High School Students’ Cognitive Learning Outcomes and Renewable Energy Literacy - Sartika Sartika; Abdul Hakim; Laili Komariyah; Riskan Qadar (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2026)
The growing global energy crisis requires younger generations to possess adequate knowledge and awareness regarding the use of renewable energy. However, students’ energy literacy remains relatively low, and instructional practices are often still conventional. This study aims to analyze the effect of the Learning Cycle 5E model on improving students' cognitive learning outcomes and energy literacy on the topic of renewable energy. A quantitative approach was employed using a quasi-experimental design with a nonequivalent control group design. The sample consisted of two Grade 10 classes from a senior high school in Samarinda, divided into an experimental group and a control group, each comprising 32 students. Data were collected through essay tests to assess cognitive learning outcomes and questionnaires to measure energy literacy. Data were analyzed using one-way ANOVA to determine the effect of the treatment. The results indicated a significant improvement in cognitive learning outcomes and students' attitudes toward energy literacy among those taught using the Learning Cycle 5E model. However, the basic knowledge and behavioral aspects did not show significant improvement, which may indicate that students had already possessed foundational environmental knowledge and pro-environmental habits influenced by the implementation of the Adiwiyata (eco-school) program. Future studies are encouraged to investigate deeper dimensions of energy literacy and to apply a longer intervention period to obtain a more comprehensive understanding of the learning model’s effectiveness in schools implementing the Adiwiyata (eco-school) program.